The Portable Medical Mentor : Training Success - Florman, Larry D. (Springer International Publishing : Imprint: Springer, 2015)
This text is directed at every student of medicine regardless of level of training or specialty ambitions. Without imparting any education in medicine per se, each chapter teaches the prospective medical trainee the art of being a physician. The reader will be convinced early on, that there is more to being a good doctor than medical school didactics. They will learn what residency admission chiefs, interviewers and faculty are most impressed with in an applicant. The first few chapters speak of the importance of, and being the best student of medicine that one can be. An extensive review of the most current government mandated laws, rules and regulations are in dedicated chapters throughout the text and can be used as a ready reference. The book brings to the reader the very up-to-date and new concepts of the ever confusing and changing realm of managed care. Additionally, one of the main purposes of this book, is to introduce to the student of medicine the use and need of advisors and mentors. This chapter entitled "Mentors" embellishes the age old tradition of true mentoring in medicine, a practice which is just now reviving itself. Medical students, trainees, and practicing physicians at all levels have had an integral part in reviewing and making the chapters more relevant to today's highly competitive and complicated playing field. The Portable Medical Mentor: Training Success addresses every facet of "how to be a good physician" in an easy to read and down to earth, practical fashion. It is intended that once read, the student will be more competitive in residency applications, better thought of as a physician, by peers, and patients, and more comfortable in their chosen specialty.